Tensile Properties of Epoxy with Microcapsules and Imidazoline Derivatives Curing Agent and Interlaminar Self-Healing Properties of Carbon Fiber Reinforced Epoxy Composites. Issue 3 (March 2014) - Hu, Honglin; Hao, Lifeng; Wang, Rongguo; Liu, Wenbo; Yang, Fan; Jiao, Weicheng; Xu, Zhonghai
Microcapsules are inevitable defects in the resin matrix, which would greatly influence on mechanical performance of structural material. Therefore, a balance value of microcapsule's content between self-healing properties and mechanical properties should be provided for fabricating adequate self-healing materials. Epoxy resin with epoxy-containing microcapsules and latent hardener 2MZ-AZINE, and carbon fiber reinforced epoxy composites were prepared. The tensile properties of epoxy resin with epoxy-containing microcapsules or 2MZ-AZINE were investigated. As the increase of content of latent hardener 2MZ-AZINE, tensile modulus and tensile stress of epoxy with 2MZ-AZINE decreases. The tensile stress of epoxy samples decreases with the enhancement of content of epoxy-containing microcapsules. Tensile modulus of epoxy with microcapsules decreases with the increase of microcapsule content below 10 wt.%, and tensile modulus increases above 10 wt.%. Considering the self-healing ability of epoxy sample, the content of microcapsules and latent hardener are concluded to 15 w% and 2 w%, respectively, offering a ∼24.7 MPa tensile stress. The maximum interlaminar self-healing efficiency in this research is only 31.98% recovery of interlaminar tensile stress (epoxy resin matrix with 15 w% microcapsule and 2 w% latent hardener 2MZ-AZINE). As a consequence, this research provided the mechanical parameter for fabricating carbon fiber reinforced epoxy composite.